Numerical Simulation of Mixing Process in a Splitting-and-Recombination Microreactor - Yan, Lifang; Wang, Shiteng; Cheng, Yi (Frontiers in Chemical Engineering, 2022)
The mixing process between miscible fluids in a splitting-and-recombination microreactor is analyzed numerically by solving Navier-Stokes equations and species transfer equations. The commercial microreactor combines rectangular channels with comb-shaped inserts to achieve splitting-and-recombination effect. The results show that the microreactor with three-layer standard inserts have the highest mixing rate as well as good mixing efficiency within a wide range of Reynolds number from 0.1 ~ 160. The size parameters of the inserts, both the ratio of the width of comb tooth (marked as l) and the spacing distance (marked as s) between two comb teeth, and the ratio of vertical distance (marked as V) of comb teeth and the horizontal distance (marked as H) are essential for influencing the liquid-liquid mixing process at low Reynolds number (e.g., Re ≤ 2). With the increase of s/l from 1 to 4, the mixing efficiency drops from 0.99 to 0.45 at Re = 0.2. Similarly, the increase in V/H is not beneficial to promote the mixing between fluids. When the ratio of V/H changes from 10:10 to 10:4, the splitting and recombination cycles reduce, so that the uniform mixing between different fluids can be hardly achieved.